Test-retest reliability of TRIMP in collegiate ice hockey players - Ulmer, J. G.; Tomkinson, G. R.; Short, S.; Short, M.; Fitzgerald, J. S. (Biology of Sport, 2019)
The utility of the heart rate derived variable TRaining IMPulse (TRIMP) for assessing internal training load in ice hockey players is not clear. Having a reliable measure of internal training load during onice training sessions would help coaches program exercise training. This study determined the reliability of TRIMP during on-ice training sessions in ice hockey players. Twelve Division I collegiate male ice hockey players (aged 18-23 years) had their heart rate (HR) data recorded during two on-ice practice sessions separated by two weeks. TRIMP and other descriptive HR variables were compared between sessions. TRIMP demonstrated moderate reliability during on-ice sessions. Systematic error, quantified as standardized change in means was negligible (-0.19); random error quantified as the percent typical error (%TE) was moderate (12.2%); and, testretest correlation was very strong (0.75). TRIMP is suitable for quantifying training load during intermittent work in hockey athletes. The results from our study can be used to determine the threshold for meaningful change in TRIMP, which may aid in informing decisions by coaches and strength training staff regarding on-ice training session difficulty and composition.